RELIGIOSITY AND HUMANITY VALUES ANALYSIS IN KURNIAWAN ARIF MASPUL'S BOOK OF SYAM DI SAAT ITU - Kurniawan Arif Maspul (JURNAL PURNAMA BERAZAM, 2022)
This paper is a study of the book "Syam Saat Itu" written by Kurniawan Arif Maspul; a collection of the author's travel notes during his one month visit to Syria in 2013 to distribute humanitarian aid from the Indonesian community through the Syrian Medical Mission (Misi Medis Suriah - MMS). When this book was written up to the time this review was compiled, Syria was a bloody conflict field that killed thousands of victims and forced millions of civilians to become refugees in various neighbouring countries and mainland Europe. This article focuses on the aspects of religion (التدين) and humanity (الانسانية) contained in the book "Syam Saat Itu". Through the book, the article reveals that in every conflict situation, we will always find alternative aspects that each party contributes to without being directly involved in the conflict.